Psychological Services to support probation in Northern Ireland and Malta. (December 2022) - Avellino, Chantal; O'Hare, Geraldine; Scicluna, Sandra
Two Probation Services, the Probation Board for N. Ireland and the Department of Probation and Parole in Malta, that directly employ Psychologists, have come together to write this article, describing how psychological services have been developed over the years to support and add value to the work of Probation services. This article will describe the development of the two services, the psychological assessments and the interventions they deliver, that enhance the work carried out by probation officers. The benefits of this specialist role within the wider justice system will also be considered. The authors will highlight key principles of good practice and the learning for probation services for the future.